Respuesta :
9(r - s) + 5(2r - 2s) = 0
perform distributive multiplication
9(r) + 9(-s) + 5(2r) + 5(-2s) = 0
9r - 9s + 10r -10s = 0
9r + 10r -9s -10s = 0
19r - 19s = 0
19r = 19s
r = 19s/19
r = s
perform distributive multiplication
9(r) + 9(-s) + 5(2r) + 5(-2s) = 0
9r - 9s + 10r -10s = 0
9r + 10r -9s -10s = 0
19r - 19s = 0
19r = 19s
r = 19s/19
r = s
ok this isn't as bad as it looks. all you have to do is multiply the terms in the parentheses by the terms outside of them. so it would b 9 x (r-s) + 5 x (2r -2s).
You would then get (9r-9s) + (10r-10s). Remove the parentheses and combine like terms. 9r + 10r is 19r and -9s plus -10s is -19s. so the answer is 19r - 19s.
You would then get (9r-9s) + (10r-10s). Remove the parentheses and combine like terms. 9r + 10r is 19r and -9s plus -10s is -19s. so the answer is 19r - 19s.